Perencanaan Strategis Bisnis Klinik Kecantikan dengan Analisa Porter’s Generic Strategy - Brigitta Isabella Bunga S; Eka Desy Purnama; Lambok D.R. Tampubolon (Journal of Management and Creative Business, 2026)
Background: The beauty industry in Indonesia is growing rapidly, increasing competition among beauty clinics. Laudi Skincare Clinic in Gombong, Kebumen, has been able to survive for 16 years amidst intense competition. Objective: This study aims to identify which of Porter's Generic Strategies is applied, evaluate its effectiveness, and provide recommendations for future business development. Method: The research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with the clinic owner, beauticians, loyal and new customers, and a supplier. Data analysis was conducted through reduction, presentation, and conclusion drawing. Results: Laudi Skincare Clinic implements the Overall Low-Cost Leadership strategy as its dominant strategy. This strategy has proven effective, as the clinic has survived for 16 years, gained loyal patients, and built a strong brand in the local community by offering affordable prices with optimal results. Supporting factors include competitive pricing, resilience to price competition, and pricing flexibility. Inhibiting factors include lack of differentiation, sensitivity to cost changes, the perception that low price equals low quality, and limitations in business development. Conclusion: The Low-Cost Leadership strategy is suitable for beauty clinics in small towns with limited purchasing power. Recommendations include adding thread lift and filler services, creating a membership program, optimizing digital marketing (Instagram, TikTok), and opening services on Sundays.